2011
DOI: 10.1007/s10853-011-5581-x
|View full text |Cite
|
Sign up to set email alerts
|

Strength variability of single flax fibres

Abstract: Due to the typical large variability in the measured mechanical properties of flax fibres, they are often employed only in low graded composite applications. The present work aims to investigate the reasons for the variability in tensile properties of flax fibres. It is found that the inaccuracy in the determination of the cross sectional area of the fibres is one major reason for the variability in properties. By applying the typical circular fibre area assumption, a considerable error is introduced into the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
61
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(70 citation statements)
references
References 23 publications
5
61
0
Order By: Relevance
“…Finally, the toughness or total energy required to break the fiber was calculated to be 22.8 ± 10.3 MJ·m −3 , higher than several natural fibers, such as flax and jute (25). The coefficient of variation in properties ranged between 30 to 50%, which is a spread commonly observed in natural fibers, including biological silk (26) and flax (27). Factors influencing variability include processing conditions (drawing speed) and environmental conditions (during processing and testing) as well as the composition of the material (26,28).…”
Section: P1mentioning
confidence: 91%
“…Finally, the toughness or total energy required to break the fiber was calculated to be 22.8 ± 10.3 MJ·m −3 , higher than several natural fibers, such as flax and jute (25). The coefficient of variation in properties ranged between 30 to 50%, which is a spread commonly observed in natural fibers, including biological silk (26) and flax (27). Factors influencing variability include processing conditions (drawing speed) and environmental conditions (during processing and testing) as well as the composition of the material (26,28).…”
Section: P1mentioning
confidence: 91%
“…Andersons et al [6] [12] tested two types of flax and have demonstrated that the fibre ultimate strain follows a Weibull distribution and derived a fibre strength distribution function. Aslan et al [13] M A N U S C R I P T…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
“…This involves the modelling of composite mechanical deformations based on the properties of each of its constituents. The steps between elemental fibres and a bundle will not be investigated as this has already been widely studied in the literature, for example Aslan et al [13], Andersons et al [6], and Thomasson et al [14]. However, there is a lack of literature investigating natural composites at a larger scale and so the smallest scale studied will be limited to the yarn.…”
mentioning
confidence: 99%
“…The relation between mechanical stress and cell wall degradation at dislocations Dislocations are mechanically weak points in the plant cell wall as they often are the locations of failure initiation (Andersons et al 2011;Aslan et al 2011). This implies that processes that introduce dislocations will make cell walls more prone to disintegration when subjected to mechanical load.…”
Section: The Reactivity Of Dislocationsmentioning
confidence: 99%